2011
DOI: 10.1016/s0924-9338(11)72024-7
|View full text |Cite
|
Sign up to set email alerts
|

The psychological profile of young people and tattoo changes

Abstract: Adolescence is a developing period on the way of forming the final identity. The core of it is the physical identity, which is the starting point and whose expression is the mirror of its internal being. Tattoos, offered as a part of fashion trend, are accepted by a great number of young people, but on the other side, many people remain distant in relation to them.The aim of workResearch carried out for determining the specificities of the psycho-social profile of adolescents with tattoos.Materials and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A particular stereotype attributed to those who aroused to tattoo concerns pathological aggression; in fact, many authors have argued that tattooed subjects tend to be more aggressive and rebellious than those who do not tattoo (Totten, Lipscomb, & Jones, 2009 ). Various researches on Serbian adolescents (Krasic, Mitic, Kostic, Ilic, & Rankovic, 2011 ) and on the island of Taiwan (Yen et al , 2012 ) have also shown, in tattooed subjects, higher levels of selfreported aggression and a greater probability of violence compared to non-tattooed subjects.…”
Section: Introductionmentioning
confidence: 97%
“…A particular stereotype attributed to those who aroused to tattoo concerns pathological aggression; in fact, many authors have argued that tattooed subjects tend to be more aggressive and rebellious than those who do not tattoo (Totten, Lipscomb, & Jones, 2009 ). Various researches on Serbian adolescents (Krasic, Mitic, Kostic, Ilic, & Rankovic, 2011 ) and on the island of Taiwan (Yen et al , 2012 ) have also shown, in tattooed subjects, higher levels of selfreported aggression and a greater probability of violence compared to non-tattooed subjects.…”
Section: Introductionmentioning
confidence: 97%